The influence of different surface texture parameters on the cell proliferation and adhesion early behaviors on the surface of titanium alloy - Lai, Fuqiang; Cao, Changsheng; Xie, Linfeng; Shang, Mingxuan; Liu, Wenge; Li, Yumei; Qiu, Zhihuang; Chen, Liangwan (Frontiers in Bioengineering and Biotechnology, 2026)
Current clinical practice has extensively validated the efficacy of left ventricular assist devices (LVADs) in managing end-stage heart failure. A persistent challenge across all ventricular assist systems involves achieving optimal biocompatibility at the critical interface between the LVAD outlet and myocardial tissue. In this study, femtosecond laser processing (FLP) technology was utilized to engineer microtextured surfaces with controlled geometric parameters on the titanium alloy surface. The experimental design systematically assessed surface morphology and compositional variations for four distinct patterns (circular, triangular, square, hexagonal) and three texture depths (10, 20, 40 μm). FLP demonstrated favourable microstructural fabrication quality, producing defined pattern boundaries with minimal thermal impact on adjacent regions. While all textured surfaces exhibited characteristic periodic processing marks at their bases, increased texture depth correlated with progressive roughness amplification in these basal regions. Elemental analysis revealed that oxygen enrichment specifically along texture peripheries compared to untextured surfaces. Cellular early response studies demonstrated that surface texturing significantly enhanced cardiac fibroblasts adhesion on titanium substrates while concurrently modifying fibroblast growth patterns. Quantitative analysis identified 20 μm as the optimal texture depth for cellular proliferation and adhesion, outperforming both shallower (10 μm) and deeper (40 μm) configurations. Geometric comparisons indicated that square patterns induced the best pronounced pro-proliferative effects, followed by hexagonal patterns. Mechanistic observations suggest that surface micro-roughness facilitates initial cell adhesion, with subsequent proliferation biodynamics being governed by topographical guidance effects. These findings establish clear structure-function relationships between engineered surface parameters and biological responses, providing significant insights for LVAD surface treatment and optimization.